Electrically Tunable Valley-Light Emitting Diode (vLED) Based on CVD-Grown Monolayer WS2 - Yang, Weihuang; Shang, Jingzhi; Wang, Jianpu; Shen, Xiaonan; Cao, Bingchen; Peimyoo, Namphung; Zou, Chenji; Chen, Yu; Wang, Yanlong; Cong, Chunxiao; Huang, Wei; Yu, Ting (Nano letters, 2016)
Owing to direct band gap and strong spin–orbit coupling, monolayer transition-metal dichalcogenides (TMDs) exhibit rich new physics and great applicable potentials. The remarkable valley contrast and light emission promise such two-dimensional (2D) semiconductors a bright future of valleytronics and light-emitting diodes (LEDs). Though the electroluminescence (EL) has been observed in mechanically exfoliated small flakes of TMDs, considering real applications, a strategy that could offer mass-product and high compatibility is greatly demanded. Large-area and high-quality samples prepared by chemical vapor deposition (CVD) are perfect candidates toward such goal. Here, we report the first demonstration of electrically tunable chiral EL from CVD-grown monolayer WS2 by constructing a p–i–n heterojunction. The chirality contrast of the overall EL reaches as high as 81% and can be effectively modulated by forward current. The success of fabricating valley LEDs based on CVD WS2 opens up many opportunities for developing large-scale production of unconventional 2D optoelectronic devices.